Switched Hybrid Control as an Alternative Energy Efficiency Technology - Flórez Vargas, Julio; Alzate Castaño, Ricardo (Ingeniería Solidaria, 2014)
This article presents hybrid control techniques as a potential solution to the problem of regulating output voltage levels from power conversion circuits to improve their energy efficiency. The example systems correspond to a dc-dc Buck converter and an ac-dc Silicon Controlled Rectifier (scr) converter. A methodology is presented for implementing hybrid control algorithms in three steps: mathematical modeling, numerical analysis, and physical implementation. Sliding Mode Control (smc) and optimal switched control are the example techniques considered. The best results in practice were obtained with the smc technique. Complementary work included the review of practical aspects to improve the performance of optimal control and the application of the methodology at greater power levels that produce effects on an industrial scale.